Thermal Maturity and Time of Oil Generation Petroleum Source Rock, Murzuq Basin (Albayan Scientific Journal, 2023)
Two consitions from Murzuqe Basin were selected to exam the source rock thermal maturity which is the main factor controlling source rock quality. These consitions are NC-115 and NC-174. Many samples were chosen from the studied consitions and analyzed for thermal maturity as well as time of oil generation. Different techniques were used here including spore colour index (SCI), vetrinite reflectance (VR), and Tmax as well as basin modelling to investigate time of oil generation of the source rock. All parameters indicate that the source rock at these consitions is at mature level and the oil was generated during Late Cretaceous to Tertiary periods.
Keywords: Thermal maturity; spore colure index; vetrinite reflectance oil generation